Evaluation of anti-ulcer and anti-oxidant activity of tephrosia calophylla by using wistar albino rats - VIMAL JOHN SAMUEL,; P. PRADEEP KUMAR, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the present study was to investigate the anti-ulcer and antioxidant activity of chloroform extract of Tephrosia calophylla (CETC) and methanolic extract of Tephrosia calophylla (METC) in albino Wistar rats by using two models namely, Pylorus ligation and Ethanol induced ulcer model. The rats were divided into five groups, each group containing six rats (n=6). Group I served as normal control, Group II ulcer control, Group III received CETC (300mg/kg.b.w.p.o), Group IV received METC (500 mg/kg. b.w.p.o), Group V Lansoprazole (30 mg/kg.b.w.p.o) two times a day for five days before gastric ulcers were induced. On 6th day ulcers were induced by the administration of ethanol and by carrying out pylorus ligation. After 1h administration of ethanol and 4h after the pylorus ligation, ulcers were scored and analyzed, and in vivo antioxidant parameters were carried out.The chloroform extract (300mg/kg) and methanolic extract (500mg/kg) showed significant inhibition of gastric lesion induced by pylorus ligation and ethanol induced ulcer models. The extracts showed reduction in ulcer index in both the models along with the reduction of ulcerative lesion, gastric volume, free and total acidity but raise in the pH of gastric juice in pylorus ligation model. There was an increase in the levels of catalase, superoxide dismutase and decrease in lipid peroxidation in in vivo antioxidant studies which shows its antioxidant properties. Thus it can be concluded that CETC as well as METC possessed antiulcer activity, which can be attributed due to its antioxidant mechanism.